1999
DOI: 10.1038/sj.bjc.6694384
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of MDR1-associated resistance to topotecan by PAK-200S, a new dihydropyridine analogue, in human cancer cell lines

Abstract: Summary Recent data suggest that expression of the membrane P 170 -glycoprotein (P-gp) may confer resistance to the topoisomerase-I-interactive agent topotecan. The present study describes the cellular effects of a new dihydropyridine analogue, PAK-200S, on P-gp-mediated resistance to topotecan in human breast and ovarian tumour cells. PAK-200S at a non-cytotoxic concentration of 2.0 µM completely reversed resistance to topotecan in P-gp-expressing MCF-7/adr (breast) and A2780/Dx5 (ovarian) tumour cells, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Because SKOV-3TR2 cell line was more resistant to TOP than SKOV-3TR1 cell line this suggested another additional mechanism responsible for TOP-resistance in this cell line. It has been reported that P-gp expression can also be related to TOPresistance (40,41). This observation was confirmed by our previous studies (16,18).…”
Section: Discussionsupporting
confidence: 80%
“…Because SKOV-3TR2 cell line was more resistant to TOP than SKOV-3TR1 cell line this suggested another additional mechanism responsible for TOP-resistance in this cell line. It has been reported that P-gp expression can also be related to TOPresistance (40,41). This observation was confirmed by our previous studies (16,18).…”
Section: Discussionsupporting
confidence: 80%
“…P-glycoprotein is encoded by the multidrug resistance 1 gene and is known to be involved in multidrug resistance, including resistance to irinotecan 29 and topotecan. 30 As shown in Figure 2B, RMG1-YR, trabectedin-resistant cells, displayed significantly greater P-gp expression than their representative parental cell lines, which strongly indicated that P-gp was involved in their trabectedin resistance. Importantly, when these cell lines were treated with SN-38 or topotecan, their P-gp expression was attenuated in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, we have observed a similar dose-dependent response pattern to topotecan in the paclitaxel resistant cell line, in spite of its low BCRP expression, which may be due to the high levels of P-gp expression in the W1PR cell line. Published reports have suggested that high levels of P-gp expression play a significant role in topotecan resistance [43]. However, two other cell lines with high expression of P-gp, W1DR and W1VR, demonstrated a sensitivity to topotecan.…”
Section: Discussionmentioning
confidence: 99%